Pelatihan Media Pembelajaran Berbasis Literasi di Ponpes Daarul Rahman Tempuling - Faridatul Munawaroh; Syarifudin Syarifudin; Dina Liana; Martina Napratilora; Nova Adi Kurniawan; Mardiah Mardiah; Rika Devianti; Hendro Lisa; Ihsan Arrasyid; Muhammad Reza (STAI Auliaurrasyidin Tembilahan, 2022)
The development of education in the world cannot be separated from the development of the industrial revolution because it indirectly changes the order of education and changes the order of learning in the classroom. Information and technology affect the activities of students and teachers. The role of the teacher, who has been the sole provider of knowledge, has shifted somewhat. The role and presence of the teacher in the classroom will be increasingly challenging and require very high innovation as the use of learning media. It is expected that literacy-based learning media as a problem solver for teachers in managing the classroom. The problem in the field is that there are still some teachers using the media in teaching the old system, most students have not been able to use the technology that has been developed at this time, most are still using the monotonous learning system, some students have not had the opportunity to learn to use the media. The method in this service uses counseling or learning media training which aims to provide understanding to teachers and students. The results that the team carried out went well according to the plans that had been prepared before the activity took place.